Analysis and synthesis of networked control systems with random network-induced delays and sampling intervals. (March 2021) - Sun, Haoyuan; Sun, Jian; Chen, Jie
Abstract: In this paper, the stability of and controller design for networked control systems (NCSs) with network-induced delays and random sampling intervals are investigated. Specifically, the network-induced delays and sampling intervals are assumed random following a joint probability density function. For stability analysis, the system is modeled in the discrete-time domain. In this context, both the moment stability and Lyapunov stability are considered, for which conditions guaranteeing stability are derived leveraging a vectorization technique. By introducing a new matrix decomposition method, the stabilization controller is designed so that the closed-loop system is stochastically stable in the presence of random sampling intervals and network-induced delays. Finally, a benchmark example is provided to validate the effectiveness of the proposed approach.